ANALISIS PERSEPSI MASYARAKAT TERHADAP PRAKTIK GOOD GOVERNANCE PEMERINTAH DAERAH - Aduwina Aduwina (Universitas Teuku Umar, 2016)
One of the aspects that central among the implementation of regional autonomy are related to segregation and amalgamation areas that aims to strengthen the relationship between government of regions and people in order growth democratic life. The practice of good governance the government the regions is an effort to strengthen democracy. It means, good governance good from the perspective of the community meaningful receive public services local governments quality .One segregation of the region is segregation of aceh barat into three areas, namely Simeulue, Nagan Raya and Aceh Jaya in 2002. At the time conflict aceh stirs that it demands the community not covered by local government services closest to the distric was segregated .In addition happened euphoria the act of regional autonomy. This study aims to analyze perceptions of Simeulue, Nagan Raya and Aceh Jaya to regional government performance in providing basic service after segregation of areas and whether there are differences between third the government the area. Survey used technique the random samples of 150 derived from three the district segregation. Of respondents about 150 terambil 58 respondents (38.7 %) of the Nagan Raya, 42 respondents ( 28.0 % ) of the Seumeulu and about 50 respondents (33.3 %) of the Aceh Jaya.Using analysis of variance (ANOVA) show services are equal treatment, there is no difference perception excessive rata-rata worth 2.1.This means public perceptions in local government services in those areas part aceh barat biasa-biasa course Keywords: Regional Autonomy, Segregation of the Region, Public Services, the Public Perception